Intellectual Property Rights (IPRS) and unemployment: empirical evidence from developing economies - Mohamad, Asuantri; Bani, Yasmin; Kaliappan, Shivee Ranjanee; Ishak, Suryati (Human Resource Management Academic Research Society, 2020)
Developing countries rely on imitation and innovation to boost their economic growth. The debate on innovation and imitation has been the focus of empirical research with the implementation of strengthening Intellectual Property Rights (IPRs). This is because IPRs may affect developing countries in terms of employment and economic growth. Theoretical studies have proven the relationship, but empirical studies on this topic are scarce. Thus, this study aims to examine the effect IPRs on unemployment in selected developing economies. System-GMM estimator is adopted by utilizing panel data for a sample of 47 developing countries from 2008-2014. This study considers the direct effect of IPRs protection on unemployment. The empirical analysis shows that stronger IPRs protection escalates unemployment in these countries as evidenced by a positive and significant relationship between these variables. As most of the technology by developing countries rely on imitation activities thus, stronger IPRs protection increases unemployment and the effect of IPRs protection on unemployment are positive.